2006
DOI: 10.1111/j.1420-9101.2006.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary sex determination in the parasitoid wasp Cotesia vestalis (C. plutellae)

Abstract: In the Hymenoptera, single locus complementary sex determination (sl‐CSD) describes a system where males develop either from unfertilized haploid eggs or from fertilized diploid eggs that are homozygous at a single polymorphic sex locus. Diploid males are often inviable or sterile, and are produced more frequently under inbreeding. Within families where sl‐CSD has been demonstrated, we predict that sl‐CSD should be more likely in species with solitary development than in species where siblings develop gregario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…However, CSD was recently demonstrated in C. glomerata (Gu and Dorn, 2003;Zhou et al, 2006), and it has been suggested to operate in C. rubecula (personal communication by Steiner in Stouthamer et al, 1992;de Boer unpublished). In addition, we have also demonstrated CSD in C. vestalis, a solitary endoparasitoid of diamond back moth larvae (de Boer et al, 2007). Diploid male survival in C. glomerata is estimated to be rather low (around 26%), whereas it appears to be relatively high in C. vestalis (approximately 70%).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, CSD was recently demonstrated in C. glomerata (Gu and Dorn, 2003;Zhou et al, 2006), and it has been suggested to operate in C. rubecula (personal communication by Steiner in Stouthamer et al, 1992;de Boer unpublished). In addition, we have also demonstrated CSD in C. vestalis, a solitary endoparasitoid of diamond back moth larvae (de Boer et al, 2007). Diploid male survival in C. glomerata is estimated to be rather low (around 26%), whereas it appears to be relatively high in C. vestalis (approximately 70%).…”
Section: Introductionmentioning
confidence: 87%
“…There are several scenarios that may reduce the genetic load associated with CSD in C. vestalis. First, we suggest that CSD in C. vestalis is based on more than one locus (de Boer et al, 2007;de Boer et al, in preparation). Under multiple locus-CSD, diploid males only develop from fertilized eggs that are homozygous at each of two or more sex loci, and the frequency of diploid males is significantly lower than under sl-CSD (Crozier, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such adaptations include the evolution of more sex loci, restored fertility of diploid males, selective fertilization of non-matched sperm in polyandrous females, avoidance of matched matings through sex-allele signaling, and others (reviewed by Cook and Crozier, 1995;van Wilgenburg et al, 2006). Evidence for most of these hypotheses is either rare (Cowan and Stahlhut, 2004 report reproductive diploid males in an aculeate wasp; De Boer et al, 2007 report multiple locus CSD in a parasitoid wasp), or completely lacking (Cook and Crozier, 1995;van Wilgenburg et al, 2006). In the largely random-mating bees, it is unclear if 244 A. Zayed adaptations reducing the cost of diploid male production would arise in normally large populations where diploid males are rare and the costs of diploid male production are low.…”
Section: Family Apidaementioning
confidence: 99%